Quantas vidas cabem numa vida? : Da autobiografia de 52 trabalhadores ao caso de um funcionário administrativo - Abrantes, Pedro (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2016)
This article is focused on the tension between unity and plurality of life pathways. How do agents conceive their lives? Do they split them in different stages and dimensions? The usefulness of recent studies on socialization and on life course are explored. An analytical framework to analyse autobiographies is sketched. An autobiography is analysed and patterns in 52 are discussed. According to this analysis, the working class in Portugal is characterized by a mitigated split of life stages and dimensions, stressing the dichotomy between work and family life, but there are multiple intersections, tensions and ambiguities, associated with poor and unstable life conditions.